中国易学发展史概要 - Sugiato Lim (Universitas Tanjungpura, 2022)
《周易》由《易》古经（卦爻辞）及《易传》组成。从孔子及其后学作《易传》开始，《周易》从卜筮之书逐渐转变为哲学著作。其发展阶段主要可分为：先秦时期——文本形成与流派确立的时期；两汉魏晋时期——理论学说与流派诠释兴起的时期；唐宋时期——学说标新与理论的高度阐发时期；元明清时期——易学的继往与开来。在发展过程中，各朝代的易学家从不同角度阐发《周易》的奥秘。让《周易》的知识体系逐渐庞大，形成易学的两派六宗，涉及占卜、象数、训诂、史学、哲学、文学、玄学、宗教学等诸多跨学科领域。几千年来《周易》一直被视为中国哲学和思想的源头。 The Book Of Changes is composed of the ancient scripture (divinatory symbols) and interpretation scripture of The Book Of Changes (Yi Zhuan). Since the Yi Zhuan written by Confucius and his later scholars, The Book Of Changes gradually changed from a book of divination to a philosophical work. Its development stages can be divided into: Pre Qin period - the period of text formation and school establishment; Han, Wei and Jin Dynasties - the period when theories and school interpretations rose; Tang and Song Dynasties - a period of theoretical innovation and high elucidation; Yuan, Ming and Qing Dynasties – the continuation anddevelopment of Yi studies. In the process of development, the Yi scholars of various dynasties expounded the mysteries of The Book Of Changes from different perspectives. Let the knowledge system of The Book Of Changes gradually expand, forming two factions and six sects in the field of Yi studies, involving divination, symbols and number, exegesis, history, philosophy, literature,metaphysics, religion and many other interdisciplinary fields. For thousands of years, The Book Of Changes has been regarded as the source of Chinese philosophy and thought.